Antidiabetic and anticancer activity of Chinese water chestnut (Eleocharis dulcis) extract with multistage extraction - Ace Baehaki; Indah Widiastuti; Susi Lestari; Masruro Masruro; Hemi Adi Putra (Wolters Kluwer Medknow Publications, 2021)
The aims of this research were to observe yield extract, phytochemical content, the antidiabetic and anticancer activity of Chinese water chestnut. This research method used an experimental laboratory, and data analysis was carried out descriptively. The stages carried of this research are sample extraction, extract yield, phytochemical analysis (flavonoid and phenolic content), antidiabetic, and anticancer activity. The results showed that the yield of extract using ethanol on Chinese water chestnut was higher than that extracts using n-hexane and ethyl acetate solvents. Phenolic and flavonoids compounds are polar so that the results of extracts with ethanol solvents show higher values than that extracts using n-hexane and ethyl acetate solvents. The result of antidiabetic activity has the highest value at a concentration of 2000 ppm using ethanol value of 65.74%. The results of the anticancer activity were expressed by (IC50), the IC50 value of the n-hexane extract was 1.231.74 ppm, ethyl acetate 941.04 ppm, and ethanol 2.261.90 ppm.